Perjalanan Omnibus Law dalam Sistem Hukum di Indonesia (Studi Tentang Penolaka Masyarakat Probolinggo Dalam Perspektif Sosiologi Hukum) - Delia Intan Hidayah; Agus Machfud Fauzi (Universitas Batanghari Jambi, 2021)
The Omnibus Law Work Creation Bill was passed by the Indonesian Parliament as a new regulation that has the power to overshadow other statutory regulations. Through this law, the government is considered to be siding with entrepreneurs or investors a lot. It is indicated that the articles in this law make people, especially workers, oppressed. Rejection actions appeared in almost all regions in Indonesia, including in Probolinggo Regency. The demonstration took place on October 8, 2020 at the Probolinggo Regency DPRD building. The mass of the action was dominated by students from the Youth Social Organization (OKP), namely HMI, PMII, GMNI, and IMM. This study is to determine the conflicts that occur in demonstrations against the Job Creation Bill and the responses of employers in responding to government policies. This study uses qualitative methods with data collection techniques for literature studies through secondary data from various sources such as articles and journals. The results of this study are, first, the students who demonstrated their 4 demands on government policies because they are detrimental to society. Second, the actions that took place chaotic, led to conflicts in society resulting in social change with deviant behavior. Third, the response of entrepreneurs to government policies, namely the government urged to focus on alleviating poverty and unemployment.